Formulation of Abelmoschus manihot Leaf Gel Using Carbopol and HPMC and Antibacterial Activity Against Pseudomonas aeruginosa - Christina Amelia; Nerly Juli Pranita Simanjuntak; Erida Novriani (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Diabetic foot ulcers are a chronic complication commonly experienced by patients with diabetes mellitus, often caused by Pseudomonas aeruginosa, a pathogenic bacterium with high antibiotic resistance. This study aimed to evaluate the effect of varying concentrations of Carbopol 940 and HPMC bases on the physical characteristics and antibacterial activity of gedi leaf (Abelmoschus manihot) extract gel preparations. The extract was obtained through maceration using 70% ethanol. The gel was formulated into six different formulas: three with HPMC (1%, 2%, and 3%) and three with Carbopol 940 (0.5%, 1%, and 2%), each containing 10% extract. Evaluations included physical characteristics (organoleptic properties, homogeneity, pH, viscosity, spreadability, and stability) and antibacterial activity against P. aeruginosa using the disk diffusion method. The results showed that all formulas met acceptable physical parameters. One-way ANOVA revealed a statistically significant difference in inhibition zone diameters among the formulas (p < 0.001). The formula containing 1% Carbopol exhibited the largest inhibition zone, indicating the most effective antibacterial activity against P. aeruginosa. These findings suggest that gedi leaf extract gel has promising potential as an alternative topical therapy for diabetic foot infections.